AB0747 Psoriatic Arthritis Registry of Turkey (PSART): Results of A Multicenter Registry on 1081 Patients. (15th July 2016) - Aydin, S.Z.; Bayindir, O.; Oksuz, M.F.; Dogru, A.; Kimyon, G.; Tarhan, E.F.; Erden, A.; Yavuz, S.; Can, M.; Cetin, G.Y.; Kilic, L.; Kucuksahin, O.; et al.
Abstract : Background: PsART (PsA registry of Turkey) is a multicenter web-based registry. Objectives: The objective of this registry is to assess characteristics of PsA and compare the differences among genders in our population. Methods: PsART was established in 2014 including 32 rheumatology centers. Detailed data regarding demographics for the skin and joint disease, disease activity assessments and treatment choices were collected. Results: One thousand and eighty-one patients (64.7% women) with a median (range) PsA duration for 3.7 (0–45) years were enrolled. Median psoriasis duration was 13 (0–59) years. The most frequent type of PsA was polyarticular 437 (40.5%) followed by oligoarticular 407 (37.7%) and axial disease 372 (34.4%). Patients with a combination of axial and peripheral disease had a longer disease duration than patients with one type of joint disease (52 (0–545) vs 42 (0–486) months, p=0.008). Mean (SD) swollen and tender joint counts were 1.7 (3) and 3.6 (4.8). 38.6% of patients were on csDMARD monotherapy, 7.1% were anti-TNF monotherapy and 22.5% were using anti-TNF plus csDMARD combinations. Within items included in the minimal disease activity, only 17.6%>67% of patients had inactive disease state. The major differences among genders were women being older (48.3 (12.8) VS 44.4 (12.5), P<0.001), more fatigue and higher HAQ scores (Table). Women also had more frequent peripheral arthritis than men and less axial disease (only peripheral vs axial vs combined, n (%): women: 479 (68.5%), 62 (8.9%), 158 (22.6%) respectively; men: 222 (59.4%), 41 (11%), 111 (29.7%) respectively; p=0.011). Women had significantly more history of psoriasis in their family compared to men (34.8% vs 25.7%, p=0.003). Conclusions: PsART had similarities with the previously published registries, supporting its external validity. Women having more fatigue and worse functioning and as well as the high percentage of active disease state point out to the unmet need in treatment of PsA. Disclosure of Interest: None declared